2021
DOI: 10.1039/d1en00185j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rhamnolipid biosurfactant on the dissolution and transport of silver nanoparticles in porous media

Abstract: The effects of nanoscale silver (nAg) particles on subsurface microbial communities can be influenced by the presence of biosurfactants, which have been shown alter nanoparticle surface properties. Batch and column...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…[44][45][46][47] Recently, Liao and coworkers investigated the effects of rhamnolipid bio-surfactants on the mobility of iron oxide nanoparticles and silver nanoparticles in saturated porous media. 48,49 They found that the presence of rhamnolipid (5-50 mg L −1 ) enhanced the transport of silver nanoparticles due to rhamnolipid adsorption onto the surfaces of silver nanoparticles, which effectively slowed the oxidation, as well as adsorption of rhamnolipid onto sand surfaces, which competed for silver nanoparticle attachment sites. 49 Moreover, Zhao et al found that 0.1% saponins signicantly enhanced the secondary transport of Pseudomonas migulae AN-1 cells due to the decreased hydrophobicity of bacteria and quartz sand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46][47] Recently, Liao and coworkers investigated the effects of rhamnolipid bio-surfactants on the mobility of iron oxide nanoparticles and silver nanoparticles in saturated porous media. 48,49 They found that the presence of rhamnolipid (5-50 mg L −1 ) enhanced the transport of silver nanoparticles due to rhamnolipid adsorption onto the surfaces of silver nanoparticles, which effectively slowed the oxidation, as well as adsorption of rhamnolipid onto sand surfaces, which competed for silver nanoparticle attachment sites. 49 Moreover, Zhao et al found that 0.1% saponins signicantly enhanced the secondary transport of Pseudomonas migulae AN-1 cells due to the decreased hydrophobicity of bacteria and quartz sand.…”
Section: Introductionmentioning
confidence: 99%
“…48,49 They found that the presence of rhamnolipid (5-50 mg L −1 ) enhanced the transport of silver nanoparticles due to rhamnolipid adsorption onto the surfaces of silver nanoparticles, which effectively slowed the oxidation, as well as adsorption of rhamnolipid onto sand surfaces, which competed for silver nanoparticle attachment sites. 49 Moreover, Zhao et al found that 0.1% saponins signicantly enhanced the secondary transport of Pseudomonas migulae AN-1 cells due to the decreased hydrophobicity of bacteria and quartz sand. 50 Considering the unique chemical structure of GO (i.e., a layered nanomaterial containing graphene sheets and abundant reactive oxygen functional groups), 1 it likely interacts with biosurfactants via van der Waals interaction, hydrogen bonding, and/or hydrophobic interaction.…”
Section: Introductionmentioning
confidence: 99%